Antifungal activity and mechanism of the antibiotic fungicide tetramycin against Magnaporthe oryzae - Jin, Huiye; Jiang, Hui; Li, Danting; Xu, Yipeng; Sun, Kai; Pang, Kun; Yu, Xiaoping; Shentu, Xuping (Frontiers in Agronomy, 2025)
Tetramycin, a polyene macrolide antibiotic known for its excellent antifungal activity, is extensively utilized in agricultural disease control. It has proven highly effective against various crop diseases, including leaf blight, black spot, and root rot. Its broad-spectrum antimicrobial activity, low toxicity, high therapeutic efficiency, and potent fungicidal properties make it a valuable tool in agriculture. This study aimed to investigate the antifungal activity of tetramycin against Magnaporthe oryzae and its underlying mechanism. The results revealed that tetramycin significantly inhibited mycelial growth in a dose-dependent manner, with a median effective concentration (EC50) of 4.41 mg·L-¹. Further investigations revealed that tetramycin markedly suppressed appressorium formation and conidial germination, reducing spore germination to 0% at high concentrations. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) observations revealed concentration-dependent morphological damage to hyphae, with severe structural alterations including contraction, deformation, fragmentation, extensive vacuolization, and cytoplasmic dilution at elevated concentrations. Cell wall integrity assays indicated no significant effect within the tested concentration range, whereas cell membrane integrity tests demonstrated that tetramycin disrupted the membrane, with the damage escalating as concentration increased. These findings suggest that tetramycin exerts its antifungal effect by compromising cell membrane integrity, leading to severe ultrastructural damage and cellular dysfunction, highlighting its potential for controlling rice blast. Future research should further elucidate its mechanism and conduct field trials to evaluate its practical application, and establish systematic resistance monitoring programs to ensure sustainable use.